Comparison of the effects of variables in sperm preparation techniques on pregnancy rates in intrauterine insemination (Annals of Medical Research, 2021)
Aim: To investigate the effects of two sperm preparation techniques, density gradient centrifugation (DGC) and swim-up, on the pregnancy rates per cycle and per group in two intrauterine (IUI) cycles. Material and Methods: The retrospective study reviewed 634 patients who presented to Firat University Medical School Hospital and underwent a total of 1,032 IUI cycles. Group I consisted of 306 (48.3%) patients who underwent a total of 524 IUI cycles between January 2012 and January 2016 and Group II included 328 (51.7%) patients who underwent a total of 508 IUI cycles between April 2015 and January 2019. The study investigated the effects of technical changes applied to sperm preparation techniques on pregnancy rates in both groups. Results:A significant difference was found between the clinical pregnancy rates of the two groups with regard to the numbers of patients and IUI cycles (p0.001). The technique used in Group II increased the pregnancy rate by 3.195 times compared to the technique used in Group I. A logistic regression analysis revealed that the pregnancy rate in the first cycle was 3.530 times higher than that of the second cycle in both groups.Conclusion: The results indicated that the application of suitable alterations in sperm preparation techniques by taking into account the potential effect of all factors is likely to affect clinical pregnancy rates in IUI.
Keywords: Intrauterine insemination; centrifugation; pregnancy rate.